2017
DOI: 10.2147/prbm.s132272
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sleep profile in schizophrenia patients treated with extended-release paliperidone: an open-label prospective study in Southeast Asia

Abstract: ObjectiveTo evaluate the effect of 6 months of treatment with paliperidone extended-release (ER) tablets on the sleep profile of patients with schizophrenia.MethodsA total of 984 patients meeting the The Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV) criteria for schizophrenia who switched their antipsychotic to paliperidone ER were recruited from 61 sites in five countries in Southeast Asia. We recorded patient demographics and assessed sleep quality and daytime drowsiness usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…Kongsakon et al . conducted an open-label prospective study evaluating the effect of six months of treatment with flexibly dosed paliperidone ER (3–12 mg daily) on sleep quality and daytime drowsiness in 984 Southeast Asian patients with schizophrenia [ 29 ]. At baseline, the mean PANSS score was 74, indicating a moderately ill population.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kongsakon et al . conducted an open-label prospective study evaluating the effect of six months of treatment with flexibly dosed paliperidone ER (3–12 mg daily) on sleep quality and daytime drowsiness in 984 Southeast Asian patients with schizophrenia [ 29 ]. At baseline, the mean PANSS score was 74, indicating a moderately ill population.…”
Section: Resultsmentioning
confidence: 99%
“…Sleep quality and daytime drowsiness were assessed using visual analog scales scored from 0–100, with higher scores indicating improved sleep quality on the sleep quality scale and more daytime drowsiness on the daytime drowsiness scale. The data found that from baseline to the end of the study, paliperidone ER statistically significantly improved sleep quality (76.44 vs. 65.48, p < 0.001) and decreased daytime drowsiness (23.18 vs. 34.22, p < 0.001) [ 29 ].…”
Section: Resultsmentioning
confidence: 99%